Methodology for Calculating the Impact of Distributed Generation on Energy Losses in a Distribution Network - Perić, Jelena D; Minić, Saša S. (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
This paper is the result of the Master’s final project “Methodology for calculating the impact of distributed generation on energy losses in a distribution network". The question is whether, for the estimation of the impact of the power plant on energy losses in the distribution network, it is necessary to analyse each hour value of small power plant engagement and its effect, or it is sufficient to analyse a small number of states, and the extent to which it is possible to reduce the number of states that will be analysed in order to review adequately the impact of the power plant on the change in energy losses of the network. To answer this question, an algorithm consisting of two steps is performed, annual production diagrams are obtained and, on the basis of calculated specific discrete values, the impact of the small power plant on energy losses in the distribution network to which it is connected is evaluated.